2020
DOI: 10.1371/journal.pone.0228450
|View full text |Cite
|
Sign up to set email alerts
|

Professional decision-making in medicine: Development of a new measure and preliminary evidence of validity

Abstract: OPEN ACCESS Citation: Antes AL, Dineen KK, Bakanas E, Zahrli T, Keune JD, Schuelke MJ, et al. (2020) Professional decision-making in medicine: Development of a new measure and preliminary evidence of validity. PLoS ONE 15(2): e0228450. https://doi.org/ 10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
0
4
0
2
Order By: Relevance
“…Finally, it should be borne in mind that the three compared samples come from different universities and socio-cultural realities: comparing people living in a metropolis (i.e., Roma) and in a relatively small town (i.e., L’Aquila) could account for possible differences in the moral judgment. Moreover, a more ecological test of moral dilemmas could be developed in augmented reality, allowing one to assess the cognitive processes underlying moral decision making in real-life contexts [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it should be borne in mind that the three compared samples come from different universities and socio-cultural realities: comparing people living in a metropolis (i.e., Roma) and in a relatively small town (i.e., L’Aquila) could account for possible differences in the moral judgment. Moreover, a more ecological test of moral dilemmas could be developed in augmented reality, allowing one to assess the cognitive processes underlying moral decision making in real-life contexts [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of the literature revealed the disparities and concerns to create a survey, while military and civilian staffs' responses to the online survey uncovered practitioners' approaches to ethical decision-making [39][40][41][42].…”
Section: Methodsmentioning
confidence: 99%
“…The method has further been explained in experimental contexts, showing that experimental strategies preserve a meaningful interpretation of main and important interaction effects [40]. Recently, the method has been used by Antes et al [41] in development of a new measure in professional decision-making in medicine.…”
Section: Design and Development Of The Survey Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…В последние годы исследования морального отчуждения охватывают и другие ситуации: насилия на свиданиях (Cuadrado-Gordillo et al, 2020), соблюдения правил в пандемию (Alessandri et al, 2020), академической прокрастинации (Wu, He, 2022). Гораздо реже изучается моральное отчуждение представителей «помогающих» профессий с дисбалансом власти: учителей (Pereira et al, 2022), врачей (Antes et al, 2020), медсестер (Fida et al, 2016). При этом данный феномен до сих пор не исследовался в контексте профессиональной деятельности психологов-консультантов и психотерапевтов, чьи профессии также являются «помогающими» и связанными с сильным дисбалансом власти в отношениях с клиентами.…”
Section: юв захарова проявление морального отчуждения у психологовunclassified